Optical design of a high-resolution spectrometer with a wide field of view. (May 2021) - Zeng, Chaobin; Han, Yan; Liu, Bin; Sun, Peng; Li, XianJing; Chen, Ping
Highlights: This optical system is a new type of integrated field of view imaging spectrometer. The structure can simultaneously obtain high resolution with a wide field of view. This new structure has the characteristics of simple structure, easy debugging. Abstract: The currently available area array imaging spectrometer fails to provide high spectral resolution and fast imaging under a wide field of view (FOV). Therefore, this study proposes an integral field imaging spectrometer (IFIS) that uses an image-space telecentric lens (ISTL), a mask, and lenslet array (MLA) as the front structure of the system. The influence of their structural parameters on the optical performance of the system is analyzed by establishing ISTL and MLA models. We selected suitable structural parameters to establish the imaging spectrometer, and provided an experimental demonstration of the system. Our system can achieve a 1.6 nm spectral resolution in a wide FOV of 48.8°. Compared with other spectrometer designs, our system is characterized by a simple structure, wider FOV, and higher spectral resolution.